An investigation into the maintenance of a third generation artificial rugby surface - Wellings, Greg (Cranfield University, 2013)
The endorsement of artificial turf for rugby by the sport’s governing bodies has seen a proliferation in facilities from grass roots to professional level. Maintenance of these facilities has become an important factor for discussion within the sports turf industry with organisations emphasising the need for well resourced, regular maintenance so that product quality and longevity may be maximised. Current knowledge and research has largely focussed on materials behaviour and the interaction of the carpet system with key playing parameters such as traction at the shoe/surface interface and surface hardness. There is comparatively little in the way of research, monitoring the longer term effects of maintenance on in-situ facilities. This research project aimed to monitor the surface quality and condition of a third generation artificial rugby pitch over an eighteen month period. A field survey was implemented to monitor key surface parameters defined in the governing body’s regulations. The results show significant differences in mean values obtained across areas of the pitch. The results assess the efficacy of maintenance operations and provide an insight into the effect of climatic conditions on surface performance and maintenance.